Introduction: Decolonial Processes in Swiss Academia and Cultural Institutions: Empirical and Theoretical Issues - Siegenthaler, Fiona; Allain Bonilla, Marie-laure (Swiss Journal of Sociocultural Anthropology, 2019)
This introduction discusses aspects of decolonial processes and their relevance with regard to Swiss cultural institutions and higher education by presenting key concepts of decolonial thinking such as coloniality, modernity and de-linking. Boaventura de Sousa Santos’s suggestions for decolonising Western universities are juxtaposed with actual decolonial processes taking place in different academic, (art) education and museum settings in Switzerland and abroad, and their political dimensions are scrutinised. The introduction concludes by presenting current debates, research projects and suggestions for practical implementation, as reflected in the contributions to the Special Issue.